Cryopreservation of euploid blastocysts obtained after fertilization of in vitro matured ovarian tissue oocytes: a case report - Kirillova, Anastasia (J Assist Reprod Genet, 2020)
With the increased rate of stable remission after gonadotoxic cancer treatment, new methods of fertility preservation are required in order to provide the best possible care for oncological patients. Here, we report an original case of euploid blastocyst cryopreservation after in vitro maturation of ovarian tissue oocytes (OTO IVM). Thirty-three oocytes were obtained from the ovarian tissue after ovariectomy in the breast cancer patient. Six out of 12 matured oocytes fertilized successfully and 3 blastocysts were formed. Genetic investigation for mutations associated with this type of malignancy found that the patient is not a carrier. Preimplantation genetic testing was performed only for aneuploidies and found all 3 blastocysts to be euploid and suitable for embryo transfer. Our study showed that the ovarian tissue oocytes matured in vitro have the potential for euploid blastocyst formation after ICSI which could be screened for aneuploidies and inherited mutations and then be vitrified in order to provide the best fertility preservation strategy for women with cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10815-020-01729-2) contains supplementary material, which is available to authorized users.